2011
DOI: 10.1177/0022466911416247
|View full text |Cite
|
Sign up to set email alerts
|

A Multiyear National Profile of Racial Disparity in Autism Identification

Abstract: Disproportionate representation of racially diverse students in special education is a well-documented problem, yet few studies have systematically evaluated disproportionate representation of diverse students with autism. This study examined disproportionate representation of racially diverse students with autism by determining risk and logistical odds ratios among racially diverse and White students from the national population between 1998 and 2006. Although overall risk of autism increased for all racial g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(49 citation statements)
references
References 26 publications
2
46
1
Order By: Relevance
“…Using special education data from the U.S. Department of Education (USDOE) from 2007-2008 academic year, Morrier and Hess (2010) found significant underrepresentation of all ethnicities (i.e., American Indian/Native Alaskan, Asian/Pacific Islander, Black/African American, Hispanic/Latino, and Caucasian) in 80 % of states under the AU eligibility category when compared to the CDC-based prevalence of ASD suggesting that, in contrast to the recommendation made by the NRC (2001), these findings indicate that not all children with ASD are provided supports and services under the AU category. Moreover, existing research strongly indicates that disproportional representation exists across races/ethnicities for children who are provided special education services under the AU category Morrier and Hess 2010;Morrier et al 2008;Travers et al 2013) in that children who are identified as belonging to traditionally underrepresented racial and ethnic groups are even less likely to be identified under the AU eligibility category than children identified as Caucasian.…”
Section: Proportional Representationmentioning
confidence: 99%
“…Using special education data from the U.S. Department of Education (USDOE) from 2007-2008 academic year, Morrier and Hess (2010) found significant underrepresentation of all ethnicities (i.e., American Indian/Native Alaskan, Asian/Pacific Islander, Black/African American, Hispanic/Latino, and Caucasian) in 80 % of states under the AU eligibility category when compared to the CDC-based prevalence of ASD suggesting that, in contrast to the recommendation made by the NRC (2001), these findings indicate that not all children with ASD are provided supports and services under the AU category. Moreover, existing research strongly indicates that disproportional representation exists across races/ethnicities for children who are provided special education services under the AU category Morrier and Hess 2010;Morrier et al 2008;Travers et al 2013) in that children who are identified as belonging to traditionally underrepresented racial and ethnic groups are even less likely to be identified under the AU eligibility category than children identified as Caucasian.…”
Section: Proportional Representationmentioning
confidence: 99%
“…To my knowledge, clusters within Somali communities in the diaspora are the first clusters discovered in racially marginalized and economically disadvantaged populations. This partially stems from disparities in the diagnosis and reporting of autism (Liptak et al 2008;Mandell et al 2009;Travers et al 2011;Baio, 2014). These racial disparities have serious consequences for poor populations and people of color because lack of access to health care and late diagnostic recognition are associated with co-occurrences of intellectual disabilities and more severe autism behaviors (Horovitz et al 2011;Chaidez et al 2012;Becerra et al 2014).…”
mentioning
confidence: 99%
“…However, through a chart review of children who are eligible for Medicaid (i.e., low socioeconomic status [SES]), Mandell and colleagues (Mandell et al, 2009;Mandell, Listerud, Levy, & Pinto-Martin, 2002) found that Black children were not diagnosed until age 7.9 years on average, 1.6 years later than the average age of diagnosis for White children. Studies have demonstrated that non-Hispanic White students with ASD are approximately 2 times more likely to be diagnosed with ASD than their Black or Hispanic peers (Kogan et al, 2009;Travers, Tincani, & Krezmien, 2013), and children from non-White minority groups are less likely than White children to have a diagnosis of ASD in their records (Mandell et al, 2009). Children born outside of the United States or to immigrant mothers are also diagnosed with ASD later than their peers (Valicenti-McDermott, Hottinger, Seijo, & Shulman, 2012).…”
mentioning
confidence: 99%